Compressive Strength and Impact Behavior of Pet Fiber Reinforced Self-Compacting Lightweight Concrete Using Expanded Polystyrene Beads As Coarse Aggregate - Almohammedi, Ahmed Abdulhakeem Shakir; Naimi, Dr. Sepanta; Al – Hadithi, Dr. Abdulkader Ismail (Migration Letters, 2023)
The behavior of self-compacting lightweight concrete (SCLWC) slabs was explored in this study. These slabs were made with waste materials acquired from the surrounding area, such as expanded polystyrene beads (EPS) and polyethylene terephthalate (PET). It can be found in large quantities in a variety of countries as municipal waste material due to the fact that it is produced every day. the Self Compacting Concrete (R mix) made of EPS content as an alternative of coarse aggregate and Six SCLWC mixtures made of EPS content as an alternative of coarse aggregate with a different Volumetric ratio of PET content (0, 0.25, 0.5, 0.75, 1.0, and 1.25%), a. An aspect ratio of 28 was applied when the PET fibers from waste plastic, which were originally made from bottles of soft drink, were incorporated into SCLWC. Additionally, the flexural behavior of SCLWC slaps was looked into as part of this investigation. The slaps were created using the same waste materials but were reinforced with one of three distinct types of bars (4, 6, or 10) and were labeled as belonging to Group A, Group B, or Group C, respectively. The addition of PET did not result much increase in the compressive strengths of SCLWC specimens, as determined by the results of an examination of the mechanical characteristics of those specimens. The low-velocity impact test was carried out using the method of repeated falling mass, and a steel ball weighing 1400g was employed in the experiment. The ball dropped freely from a height of 2400 mm onto concrete panels measuring 500 mm by 500 mm by 50 mm and featuring a mesh made of discarded plastic fiber. According to the results that were acquired in the past, the number of strikes that generated the initial fracture as well as the last crack (failure) was determined. When compared with the reference mix, the mixes that contained plastic fibers exhibited superior increases in their respective mechanical properties.